Identifikasi Penyebaran Dan Ketebalan Batubara Menggunakan Metode Geolistrik Resistivitas - Tony Yulianto; Sugeng Widodo (BERKALA FISIKA, 2012)
A Geoelectricity survey using Schlumberger configuration has been conducted in area X of Muara Muntai district, Kutai Kertanegara dictric East Borneo using Schlumberger configuration to probe the existence of coal. Modeling using matching curve to describe subsurface in X area base on 11 points sounding from field data acquisition The result indicates that the coal is within the depth of 60m-70m with a thickness of 1m-2m. Whereas the value of coal resistivity is in the reach 90 Ώm-120 Ώm. It can be then concluded that area X is not prospecting to exploitation. Keyword: Schlumberger configuration, coal, resistivity